Spectral characterization of materials using terahertz time domain spectroscopy (THz-TDS) - Hissen, Huzifa Zain Alabdeen Abdarahman (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2014.